Heat exchanger member, heat exchanger, cooling system
Patent Information
- Application Number
- CN202180003396.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-17
- Filing Date
- 2021-03-02
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-03-02
AI Technical Summary
[0003]另一方面,近年来,半导体器件处理的信息量和速度进一步提高,作为其对策的高集成化产生对应的冷却系统的设置限制和耗电量的增大
[0015]根据本发明,可实现对热交换器用构件附加使热交换器的液化以及气化效率提高的功能的效果。
Smart Images

Figure CN113841022B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a component for a heat exchanger that imparts properties to the surface of a metal other than the inherent properties of the metal and uses a refrigerant with a better cooling effect than water, as well as a device having the component. Background Technology
[0002] In a cooling system using refrigerant, the refrigerant circulates within the system. In the cooling section, the object is cooled by the vaporization of the refrigerant flowing in the heat exchanger. In the heat exchanger of the heat dissipation section, the refrigerant is cooled and liquefied by external air or the like. In the aforementioned cooling system, the efficiency of releasing heat to the outside and liquefying the refrigerant in the heat exchanger of the heat dissipation section (hereinafter referred to as liquefaction efficiency), the efficiency of vaporizing the refrigerant and carrying away heat in the heat exchanger of the cooling section (hereinafter referred to as vaporization efficiency), and the pressure loss of the refrigerant flowing in the pipes determine the size of the system and the energy consumption of the pump that circulates the refrigerant.
[0003] On the other hand, in recent years, the amount of information processed and the speed of semiconductor devices have further increased, and the high integration as a countermeasure has led to corresponding limitations in the setting of cooling systems and an increase in power consumption.
[0004] Therefore, in order to improve the flexibility of cooling system design and reduce energy consumption, technologies related to liquefaction efficiency, vaporization efficiency, and pressure loss reduction are being researched. For example, such a technology is disclosed in Patent Document 1.
[0005] Patent Document 1 describes a method that improves the vaporization efficiency of the cooling section and the liquefaction efficiency of the heat dissipation section by adding a gas-liquid separation section to the cooling system.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent Application Publication No. 2004-190928 Summary of the Invention
[0009] The problem the invention aims to solve
[0010] However, in the technology of Patent Document 1, an additional gas-liquid separation unit needs to be added to the cooling system, which results in limitations on the configuration of the cooling system and a significant increase in cost.
[0011] The present invention was made in view of the above-mentioned problems, and its object is to endow the surface of the metal in contact with the refrigerant in a heat exchanger used in a cooling section or heat dissipation section with properties that the metal itself does not have by means of a film with excellent thermal conductivity and excellent wettability with the refrigerant, thereby realizing a high-efficiency heat exchanger component, heat exchanger, and cooling system.
[0012] means for solving problems
[0013] To solve the above-mentioned problems, the heat exchanger component of the present invention is made of metal, and when the heat exchanger manufactured using the heat exchanger component is in operation, it has a surface in contact with the refrigerant, and the surface has a metal oxide film, the metal oxide film contains crystalline carbon and is provided with protrusions, the average interval between the vertices of the protrusions is 20 nm or more and 80 nm or less, the average height of the vertices of adjacent protrusions is 10 nm or more and 70 nm or less, and the aspect ratio of the average height divided by the average interval is less than 1.
[0014] The effects of the invention
[0015] According to the present invention, it is possible to achieve the effect of adding a component to a heat exchanger to improve the liquefaction and vaporization efficiency of the heat exchanger. Attached Figure Description
[0016] Figure 1 This is a schematic diagram showing a semiconductor cooling system using a heat exchanger component according to the first embodiment of the present invention.
[0017] Figure 2 This is a diagram illustrating a heat exchanger component according to a first embodiment of the present invention.
[0018] Figure 3 It shows along Figure 2 The arrow aa is a schematic diagram of the cross-section observed.
[0019] Figure 4 This is the AFM observation result of the refrigerant contact surface of the heat exchanger component according to the first embodiment of the present invention.
[0020] Figure 5 This is a diagram illustrating an apparatus used to manufacture a first embodiment of the present invention.
[0021] Figure 6 This is a graph showing a time chart for producing the loaded electrolytic density of the first embodiment of the present invention.
[0022] Figure 7 This is a diagram illustrating a liquefaction test of the first embodiment of the present invention.
[0023] Figure 8 This is a SEM perspective view of the first embodiment of the present invention.
[0024] Figure 9 This is a SEM perspective view of a comparative example of the first embodiment of the present invention.
[0025] Figure 10 This is a diagram illustrating a heat exchanger component according to a second embodiment of the present invention.
[0026] Figure 11 It shows along Figure 10 The arrow aa is a schematic diagram of the cross-section observed.
[0027] Figure 12 This is the AFM observation result of the refrigerant contact surface of the heat exchanger component according to the second embodiment of the present invention.
[0028] Figure 13 This is a diagram illustrating an apparatus used to manufacture a second embodiment of the present invention.
[0029] Figure 14 This is a graph showing a time chart for producing the loaded electrolytic density of the second embodiment of the present invention.
[0030] Figure 15 This is a diagram illustrating a cooling test of the second embodiment of the present invention.
[0031] Figure 16 This is a SEM perspective view of the second embodiment of the present invention.
[0032] Figure 17 This is a SEM perspective view of a comparative example of the second embodiment of the present invention. Detailed Implementation
[0033] (First Implementation)
[0034] The following is based on Figures 1-9 The embodiments of the present invention are described below.
[0035] <Structure of a semiconductor cooling system with mounted components>
[0036] Figure 1 This is a schematic diagram of a semiconductor cooling system 100. The semiconductor cooling system 100 consists of a cooling section (heat exchanger) 110, a heat dissipation section (heat exchanger) 120, a compressor 130, an expansion valve 140, etc.
[0037] The heat dissipation unit 120 consists of a heat exchanger 121 and a fan 122. Inside the heat exchanger 121, the heat released during refrigerant liquefaction is dissipated to the outside of the system via the fan 122. The heat exchanger component of the present invention refers to the component constituting the heat exchanger 121. In the following description, the heat exchanger component will be described as the pipe that internally liquefies the refrigerant, i.e., the component constituting the heat exchanger 121.
[0038] <Structure of Components>
[0039] Figure 2 as well as Figure 2 The aa cross section diagram is Figure 3This is a diagram illustrating a specific example of the components for a heat exchanger according to the present invention, namely the tubes constituting the heat exchanger 121. (See diagram for details.) Figure 3 As shown, a crystalline carbon-containing oxide film 121C is formed on a metal substrate 121A made of the main material of the tube (aluminum, stainless steel, copper, etc.), and tiny protrusions 121B are provided on the crystalline carbon-containing oxide film 121C. The crystalline carbon-containing oxide film 121C with these tiny protrusions 121B is a metal oxide film containing crystalline carbon, which has the following functions: improving the wettability of the inner surface of the tube in contact with the refrigerant, which is a gas, in the heat exchanger 121, and improving the efficiency of cooling the refrigerant by means of the high thermal conductivity of the contained crystalline carbon.
[0040] The pipe is made of metal tubing such as aluminum, stainless steel, or copper. The wall thickness and length of the pipe are not particularly limited and are determined appropriately according to the intended use.
[0041] The crystalline carbon-containing oxide film 121C is an oxide containing crystalline carbon and made of the same or identical metal as the metal substrate material. The thickness of this crystalline carbon-containing oxide film 121C can be 10 nm to 300 nm. Furthermore, to fully utilize the thermal conductivity of the contained crystalline carbon and improve liquefaction efficiency, the thickness of the crystalline carbon-containing oxide film 121C is preferably 100 nm to 300 nm. At a distance of 3 nm to 5 nm from the surface (the opposite side of the surface in contact with the metal substrate 121A), the carbon content ratio in the carbon-containing oxide film 121C is preferably 5 at% to 50 at%. Moreover, to possess the properties imparted by the presence of crystalline carbon and maintain the strength of the film, the crystalline carbon content ratio in the carbon-containing oxide film 121C at a distance of 3 nm to 5 nm from the surface is preferably 8 at% to 40 at%.
[0042] To improve thermal conductivity, the crystalline carbon contained in the 121C crystalline carbon oxide film is preferably carbon nanotubes, fullerenes, graphene, etc.
[0043] Micro protrusions 121B are disposed on the surface of the crystalline carbon oxide film 121C (opposite to the surface in contact with the metal substrate 121A). The average interval between adjacent vertices of the micro protrusions 121B is more than 20 nm and less than 80 nm. The average height of the vertices of the protrusions is more than 10 nm and less than 70 nm. The aspect ratio of the average height divided by the average interval is less than 1.
[0044] Furthermore, in order to impart higher wettability with the refrigerant, the micro protrusion 121B preferably has an average spacing of 25 nm or more and 65 nm or less between adjacent vertices, an average height of vertices of the protrusion of 15 nm or more and 55 nm or less, and the aspect ratio of the average height divided by the average spacing is less than 0.83.
[0045] The following is based on Figures 5-8 An embodiment of the first embodiment is described. The heat exchanger 121 in the embodiment is made of an aluminum tube with an outer diameter of 8 mm (inner diameter of 6 mm) × 220 mm. In order to form a crystalline carbon oxide film 121C with tiny protrusions 121B on the inner surface of the aluminum tube (metal substrate 121A), the following treatment is performed.
[0046] First, the aluminum tube (metal substrate 121A) is degreased by immersion in ethanol (immersion time: 30 minutes). Then, as... Figure 5 As shown, an aluminum tube connected to circuit 400 and an electrode 404 are immersed in a bath 300 containing treatment solution 301, with the electrode 404 inserted in such a way that it does not contact the inner surface of the aluminum tube. The electrode 404 is located inside the aluminum tube and connected to circuit 400, and is made of SUS304 (304 stainless steel). Regarding the treatment solution 301 in the bath 300, sodium hydroxide and 0.2% of a single-walled carbon nanotube dispersion dispersed in purified water by means of a dispersant are added to the purified water to achieve concentrations of 0.85 g / L and 1.35 ml / L, respectively, and the temperature is adjusted to reach 30°C.
[0047] Then, the current is directed along... Figure 6 The direction of the arrow shown indicates the flow pattern, which is considered as the positive direction of the current. Figure 6 As shown, voltage is applied to the aluminum tube via rectifiers 401 and 402 and switching switch 403.
[0048] Finally, the material is washed with water and dried in a constant temperature bath (80°C, 30 minutes). This process creates a 200nm crystalline carbon oxide film 121C on the surface of the aluminum tube (metal substrate 121A), while simultaneously creating micro-protrusions 121B on the surface of the crystalline carbon oxide film 121C. Figure 4 The average spacing between the vertices of adjacent micro-protrusions 121B is 61 nm, and the average height of the micro-protrusions 121B is 50 nm, thus constituting a heat exchanger 121.
[0049] <Verification Experiment>
[0050] Here, we will explain the required characteristics of the heat exchanger in the heat dissipation section. The heat exchanger in the heat dissipation section liquefies the refrigerant by taking heat from the refrigerant, which is vaporized in the cooling section and compressed into a high-temperature, high-pressure gaseous state by the compressor, and dissipating it to the outside. At this point, all the refrigerant needs to be liquefied in a manner that allows it to circulate within the system. Therefore, if the liquefaction efficiency per unit area of refrigerant contact with the heat exchanger deteriorates, the size of the heat exchanger will naturally increase, limiting the installation of the cooling system and significantly increasing costs.
[0051] Furthermore, in general, the heat dissipation section is larger than the cooling section in semiconductor cooling systems; therefore, the liquefaction efficiency affects the overall size and cost of the unit. Thus, for the heat exchanger in the heat dissipation section, it is necessary to improve the liquefaction efficiency.
[0052] For the tube constituting the heat exchanger of the present invention, the contact angle, which represents the wettability with the refrigerant (such as fluorocarbons or mixtures of methyl nonafluorobutyl ether and methyl nonafluoroisobutyl ether), can be very small. For example, in the case of aluminum, by configuring it as in the present invention, the contact angle can be reduced from an untreated 4.18° to 0.67°, thus facilitating refrigerant flow and recovery. Furthermore, the structure of the present invention contains crystalline carbon with excellent thermal conductivity, such as carbon nanotubes, resulting in excellent heat exchange performance. Therefore, the heat exchanger of the present invention exhibits excellent liquefaction efficiency.
[0053] like Figure 7 As shown, outside the constant temperature bath 510, Figures 2-4 , Figure 8 The heat exchanger 121 of the present invention shown (with a contact angle of 0.67° with the refrigerant and a crystalline carbon content of 10% (at a distance of 5 nm from the surface)) and the comparison device with an inner surface of... Figure 9 A heat exchanger 522, made of untreated aluminum tubing with the same shape as in this invention (with a contact angle of 4.18° with the refrigerant and a crystalline carbon content of 0% (at a distance of 5 nm from the surface)), is connected to silicone tubing 541 and 542. Silicone tubing 541 and 542 are connected to refrigerant containers 531 and 532, which are positioned within... Figure 7 The liquefaction characteristic evaluation device 500 shown is housed in a constant temperature bath 510 and is sealed with refrigerant.
[0054] Then, by operating the thermostatic bath 510 to reach 70°C, the refrigerant in the refrigerant containers 531 and 532 is evaporated. The refrigerant vaporized in each heat exchanger 121 and 522 is introduced. The refrigerant cooled and liquefied at room temperature (15°C) is recovered through the recovery containers 551 and 552. The weight of the liquefied refrigerant is measured and divided by the weight of the refrigerant entering the refrigerant containers 531 and 532, thereby deriving the liquefaction efficiency.
[0055] As a result, it was confirmed that the liquefaction efficiency of the heat exchanger 121 of the present invention is 71.1%, which is higher than the liquefaction efficiency of 59.8% of the untreated heat exchanger 522 used for comparison.
[0056] Furthermore, in this embodiment, a wet electrolytic process under the conditions described above was used to form a crystalline carbon oxide film 121C with minute protrusions 121B on its surface. However, this method is not limited to this; it can also be formed under other conditions or by other processing methods (such as sputtering using a metal oxide target containing carbon nanotubes or the sol-gel method). However, the wet electrolytic process is superior to other processing methods in terms of cost.
[0057] In this way, compared with conventional mechanisms that add gas-liquid separation units and other mechanisms, the heat exchanger 121 of the present invention (or a component for heat exchangers) can achieve the following effects: it can reduce the overall size of the cooling system, relax the installation restrictions, and does not involve major changes. Therefore, the parts associated with the cooling system do not need to be changed, thereby suppressing cost increases.
[0058] Furthermore, the first embodiment of the present invention is not limited to a tube-shaped component that constitutes a heat exchanger 121. It may also be a component that constitutes a partition wall provided inside the heat exchanger for cooling the refrigerant or an internal fin, etc. In any case, the same effect as the component that constitutes the heat exchanger 121 can be achieved.
[0059] Furthermore, a heat exchanger consisting of components that constitute the heat exchanger 121, components that constitute a partition wall provided inside the heat exchanger for cooling the refrigerant, internal fins, and other components can of course achieve the same effect as the heat exchanger 121.
[0060] Furthermore, the cooling system equipped with a heat exchanger made of the components of the embodiments of the present invention can obviously achieve the same effect as the heat exchanger 121 described above. Therefore, the following effects can be achieved: the overall size of the cooling system can be reduced, the installation restrictions can be relaxed, and there are no major changes. Therefore, the parts associated with the cooling system do not need to be changed, thereby suppressing the increase in cost.
[0061] (Second Implementation)
[0062] The following is based on Figures 10-17 The embodiments of the present invention are described below.
[0063] <Structure of a semiconductor cooling system with mounted components>
[0064] Figure 1 This is a schematic diagram showing a semiconductor cooling system 100. The semiconductor cooling system 100 consists of a cooling section 110, a heat dissipation section 120, a compressor 130, an expansion valve 140, etc.
[0065] The cooling section 110 consists of a heat exchanger 111 and a semiconductor 150. Inside the heat exchanger 111, when the refrigerant is vaporized, the heat generated in the semiconductor 150 is removed, and the semiconductor 150 is cooled. The heat exchanger component of the present invention refers to the component constituting the heat exchanger 111. In the following description, the heat exchanger component will be described as the pipe that vaporizes the refrigerant inside, i.e., the component constituting the heat exchanger 111.
[0066] <Structure of Components>
[0067] Figure 10 as well as Figure 10 The aa cross section diagram is Figure 11 This is a diagram illustrating a specific example of the components for a heat exchanger according to the present invention, namely the tubes constituting the heat exchanger 111. Figure 11 As shown, a crystalline carbon-containing oxide film 111C is formed on a metal substrate 111A made of the main material of the tube (copper, aluminum, stainless steel, etc.), and tiny protrusions 111B are provided on the crystalline carbon-containing oxide film 111C. The crystalline carbon-containing oxide film 111C with these tiny protrusions 111B is a metal oxide film containing crystalline carbon, which, in the heat exchanger 111, provides the following functions: improving the wettability of the inner surface of the tube in contact with the refrigerant, which becomes liquid, and increasing the contact area with the refrigerant even when the refrigerant begins to vaporize during cooling; furthermore, the presence of crystalline carbon with a high thermal conductivity increases the thermal conductivity, thereby improving the heat transfer efficiency (vaporization efficiency) of the refrigerant transferred from the semiconductor 150 through the heat exchanger 111.
[0068] The pipe is made of metal tubing such as copper, aluminum, or stainless steel. The wall thickness and length of the pipe are not particularly limited and are determined appropriately according to the intended use.
[0069] The crystalline carbon oxide film 111C is an oxide containing crystalline carbon and made of the same or identical metal as the metal substrate material. The thickness of this crystalline carbon oxide film 111C can be 10 nm to 300 nm. Furthermore, to fully utilize the thermal conductivity of the contained crystalline carbon and improve vaporization efficiency (i.e., the efficiency of transferring heat from the semiconductor to the refrigerant), the thickness of this crystalline carbon oxide film 111C is preferably 100 nm to 300 nm. At a distance of 3 nm to 5 nm from the surface (the opposite side of the surface in contact with the metal substrate 121A), the carbon content ratio in this carbon oxide film 121C is preferably 5 at% to 50 at%. Moreover, to possess the properties imparted by the presence of crystalline carbon and maintain the strength of the film, the crystalline carbon content ratio in this carbon oxide film 121C at a distance of 3 nm to 5 nm from the surface is preferably 8 at% to 40 at%.
[0070] To improve thermal conductivity, the crystalline carbon contained in the 111C crystalline carbon oxide film is preferably carbon nanotubes, fullerenes, graphene, etc.
[0071] The micro protrusions 111B are disposed on the surface of the crystalline carbon oxide film 111C (the opposite side of the surface in contact with the metal substrate 111A). The average interval between adjacent vertices of the micro protrusions 111B is more than 20 nm and less than 80 nm. The average height of the vertices of the protrusions is more than 10 nm and less than 70 nm. The aspect ratio of the average height divided by the average interval is less than 1.
[0072] Furthermore, in order to impart higher wettability with the refrigerant, the micro protrusion 111B preferably has an average spacing of 25 nm or more and 65 nm or less between adjacent vertices, an average height of vertices of the protrusion of 15 nm or more and 55 nm or less, and the aspect ratio of the average height divided by the average spacing is less than 0.83.
[0073] The following is based on Figures 13-16 An embodiment of the second implementation is described. The heat exchanger 111 in the embodiment is based on... Figure 15 As shown, there is an opening in the center. A 11mm square copper rod with a through hole and a length of 50mm is fabricated. This is for the purpose of... The surface of the pore is provided with a crystalline carbon-containing oxide film 111C with tiny protrusions 111B, and then the following treatment is performed.
[0074] First, the square copper rod (metal substrate 111A) was degreased by immersion in ethanol (immersion time: 30 minutes). Then, as... Figure 13 As shown, a square copper rod connected to circuit 600 and an electrode 604 are inserted in a bath 700 containing treatment solution 701, with the electrode 604 inserted in such a way that it does not contact the inner surface of the hole in the square copper rod. The electrode 604 is located inside the square copper rod and connected to circuit 600, and is made of SUS304 (304 stainless steel). Regarding the treatment solution 701 in the bath 700, sodium hydroxide and 0.2% of a single-walled carbon nanotube dispersion dispersed in purified water by means of a dispersant are added to the purified water to achieve concentrations of 0.85 g / L and 1.35 ml / L, respectively, and the temperature is adjusted to reach 30°C.
[0075] Then, when the current is along Figure 14 The direction of the arrow shown indicates the flow pattern, which is considered as the positive direction of the current. Figure 14 As shown, voltage is applied to the aluminum tube via rectifiers 601 and 602 and switching switch 603.
[0076] Finally, the sample is washed with water and dried in a constant temperature bath (80°C, 30 minutes). This process creates a 150nm crystalline carbon-containing oxide film 111C on the surface of the square copper rod (metal substrate 111A), while simultaneously creating micro-protrusions 111B on the surface of the crystalline carbon-containing oxide film 111C. Figure 12 The average spacing between the vertices of adjacent micro-protrusions 111B is 30.0 nm, and the average height of the micro-protrusions 111B is 16.4 nm, thus forming a heat exchanger 111.
[0077] <Verification Experiment>
[0078] Here, we will explain the required characteristics of the heat exchanger in the cooling section. In the heat exchanger of the cooling section, the refrigerant, which liquefies in the heat dissipation section and becomes a low-temperature, low-pressure liquid after passing through the expansion valve, receives heat generated by the semiconductor being cooled and vaporizes, thereby achieving cooling. At this time, if the heat generated in the semiconductor cannot be effectively removed, the temperature of the semiconductor will rise and eventually be destroyed. On the other hand, in recent years, the integration density of semiconductors has become increasingly higher, and therefore, the heat generated during operation has gradually increased. Therefore, it is necessary to liquefy all the refrigerant in a way that improves the efficiency of refrigerant vaporization and heat removal (hereinafter referred to as vaporization efficiency) within the system. Therefore, if the liquefaction efficiency per unit area of refrigerant contact in the heat exchanger deteriorates, the size of the heat exchanger will naturally increase, which will limit the installation of the cooling system and significantly increase the cost.
[0079] Moreover, in general, in semiconductor cooling systems, the heat dissipation section is larger than the cooling section, so the vaporization efficiency affects the overall size and cost of the unit.
[0080] Therefore, for heat exchangers in the cooling section, it is necessary to improve the efficiency of vaporizing the refrigerant and removing heat (vaporization efficiency), i.e., the heat transfer coefficient to the refrigerant.
[0081] Furthermore, with increasing integration, the heat generated within the semiconductor causes the refrigerant to vaporize near the semiconductor, resulting in burnout that cannot be cooled regardless of the amount of refrigerant flowing through it. This has become a major limiting factor for semiconductor integration. Therefore, it is necessary to improve both the heat transfer coefficient and the critical heat flux at which burnout occurs.
[0082] The contact angle representing the wettability with the refrigerant (such as fluorocarbons or a mixture of methyl nonafluorobutyl ether and methyl nonafluoroisobutyl ether) on the inner surface of the hole in the square rod constituting the heat exchanger 111 of the present invention can be very small. For example, in the case of copper, by configuring it as in the present invention, the contact angle can be changed from an untreated 5.72° to 1.77°. Therefore, even if the refrigerant begins to vaporize, heat is effectively transferred because the refrigerant can contact the inner surface of the hole with a larger area. In addition, the structure of the present invention contains crystalline carbon with excellent thermal conductivity, such as carbon nanotubes, thus further improving heat exchange performance. Therefore, the heat exchanger of the present invention has excellent vaporization efficiency (heat transfer coefficient).
[0083] Will Figures 10-12 , Figure 16 The heat exchanger 111 of the present invention shown (with a contact angle of 1.77° with the refrigerant and a crystalline carbon content of 12% (at a distance of 5 nm from the surface)) and the comparison device with an inner surface such as Figure 17 Heat exchangers 911, constructed from untreated square copper rods of the same shape as those in this invention (with a contact angle of 5.72° with the refrigerant and a crystalline carbon content of 0% (at a distance of 5 nm from the surface)), are alternately arranged. Figure 15 The measuring section of the vaporization characteristic evaluator 800 shown has a ceramic heater 151 or 152 that looks like a semiconductor placed on the upper surface of the heat exchangers 111 and 911.
[0084] Then, the pump of the vaporization characteristic evaluator 800 is operated to circulate the refrigerant within the vaporization characteristic evaluator. Based on this, the output of the ceramic heater is increased, and the temperature of each part is measured. From this, the heat transfer coefficient and critical heat flux of the heat exchanger 111 of the present invention and the untreated heat exchanger 911 used for comparison with the refrigerant are derived.
[0085] As a result, the heat transfer coefficient of the heat exchanger 111 of the present invention was confirmed to be 6.72 W / (m²). 2 K), the critical heat flux is 4.47 W / m 2 The heat transfer coefficient of the untreated heat exchanger 911 used for comparison is 5.82 W / (m²). 2 K), and critical heat flux 4.32 W / m 2 In comparison, both have been improved.
[0086] Furthermore, in this embodiment, a wet electrolytic process under the conditions described above was used to form a crystalline carbon oxide film 111C with minute protrusions 111B on its surface. However, this method is not limited to this; it can also be formed under other conditions or by other processing methods (such as sputtering using a metal oxide target containing carbon nanotubes or the sol-gel method). However, the wet electrolytic process is superior to other processing methods in terms of cost.
[0087] Thus, compared with the conventional heat exchanger 911 that does not treat the contact surface with the refrigerant, the heat exchanger 111 (also a component for heat exchangers) of the present invention has a superior heat transfer coefficient (vaporization efficiency), so the following effects can be achieved: the overall size of the cooling system can be reduced, the installation restrictions can be relaxed, and the critical heat flux can also be improved, thereby enabling the expansion limits of semiconductor integration.
[0088] Furthermore, the second embodiment of the present invention is not limited to the perforated square rod-shaped component that constitutes the heat exchanger 111. It may also be a component that constitutes a partition wall provided inside the heat exchanger for vaporizing the refrigerant or an internal fin, etc. In any case, the same effect as the component that constitutes the heat exchanger 111 can be achieved.
[0089] In addition, a heat exchanger consisting of components that constitute the heat exchanger 111, components that constitute a partition wall provided inside the heat exchanger for vaporizing the refrigerant, or internal fins can of course achieve the same effect as the heat exchanger 111.
[0090] Furthermore, the cooling system equipped with a heat exchanger made of the components of the embodiments of the present invention can obviously achieve the same effect as the heat exchanger 111 described above. Therefore, the following effects can be achieved: the overall size of the cooling system can be reduced, the installation restrictions can be relaxed, and there are no major changes. Therefore, the parts associated with the cooling system do not need to be changed, thereby suppressing the increase in cost, and the integration limit of semiconductors can also be updated.
[0091] Furthermore, it has been confirmed that the inner surface of the component (pipe) in the embodiment of the present invention can reduce the pressure loss during refrigerant circulation in a state of liquid and gas mixing in the cooling system. For example, compared with the case where the pressure loss is not treated, by treating the inner surface of the stainless steel pipe as performed in Examples 1 and 2, the pressure loss can be reduced by 37% when the volume mixing ratio of gas and liquid is 30%.
[0092] Therefore, it achieves the effect of reducing the energy consumption of the pump used to circulate the refrigerant.
[0093] This invention is not limited to the embodiments described above, and various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in the various embodiments are also included within the technical scope of this invention. Furthermore, by combining the technical means disclosed in the various embodiments, new technical features can be formed.
[0094] Industrial availability
[0095] This invention can be used in components for heat exchangers that require improved liquefaction and / or gasification characteristics.
[0096] Explanation of reference numerals in the attached figures
[0097] 100: Semiconductor cooling system
[0098] 121: Heat exchanger (heat dissipation unit)
[0099] 121A: Metal substrate,
[0100] 121B: minute protrusions,
[0101] 121C: Crystalline carbon oxide film (metal oxide film)
[0102] 300: Bathtub,
[0103] 400: Circuit.
Claims
1. A heat exchanger component comprising a metal substrate made of metal and a metal oxide film containing crystalline carbon disposed on the metal substrate, the heat exchanger component being used as a heat exchanger for receiving heat generated from a cooled object and vaporizing a liquid refrigerant, characterized in that, The surface of the metal oxide film that comes into contact with the liquid refrigerant when the heat exchanger is operating is provided with a protrusion. The average spacing between the vertices of the protrusions is greater than 20 nm and less than 80 nm. The average height of the apex of adjacent protrusions is greater than 10 nm and less than 70 nm. Furthermore, the aspect ratio of the average height divided by the average interval is less than 1. The content of crystalline carbon in the range of 3-5 nm from the surface of the metal oxide film is 20 at% to 40 at% or more. The contact angle between the metal oxide film and the refrigerant, which indicates the wettability of the refrigerant to the metal oxide film having the protrusions, is smaller than the contact angle between the metal substrate and the refrigerant, which indicates the wettability of the refrigerant to the metal substrate. Even if the refrigerant begins to vaporize, it increases the contact area between the metal oxide film and the refrigerant, thereby improving the vaporization efficiency of the refrigerant.
2. The heat exchanger component according to claim 1, characterized in that, The thickness of the metal oxide film is greater than 100 nm and less than 300 nm.
3. A heat exchanger, characterized in that, The heat exchanger component as described in claim 1 or 2 is provided.
4. A cooling system, characterized in that, The heat exchanger as described in claim 3 is provided.
Citation Information
Patent Citations
Boiling cooling medium forcible circulation type semiconductor cooling device
JP2004190928A
Fin for heat exchanger
JP1998026491A
Heat exchanger
JP2006242390A
HEAT TRANSFER DEVICE AND SYSTEM INCLUDING SAME
JP2009503432A
Metallic member, heat exchanger, air conditioner and refrigerator
JP2019167622A
